Kreowanie ról przez uczestników gier RPG - perspektywa interakcjonizmu symbolicznego = Role creation by RPG players - the symbolic interactionism perspective - Kaźmierczak-Kałużna, Izabela (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article explores the analogy between character creation and role-playing by RPG players and the construction of social roles by individuals in everyday life. Drawing on the theoretical foundations of symbolic interactionism, particularly the works of G.H. Mead and E. Goffman, the author highlights the parallels between these processes, emphasising how role-playing games can be perceived - and potentially employed ? as a platform or tool for enhancing individuals` social skills.
Keywords: rola społeczna; kreowanie ról społecznych; aktor społeczny; interakcjonizm symboliczny; gry RPG; gracz; social roles; social role creation; social actor; symbolic interactionism; player